(untitled) (Lapai Journal of Economics, 2024)
The advent and increasing households’ uptake of digital credit (an unsecured high interest loan provided through digital channels with little or no knowledge of the conditionality of the credit by the up takers) in recent times has been accompanied with mounting household over indebtedness. This study investigated the impact of digital micro-credit and financial literacy on households’ over-indebtedness in Niger state Nigeria. Using multi-stage sampling technique three (3) Local Government Areas were selected from each of the cluster of the three senatorial districts of the state, a purposive sample size of 462 respondents was used for the analysis. Finding reveals that easy access, no collateral demanded on taking the loan, and poor financial/credit knowledge were the major causes of their over indebtedness. The study hence recommends that digital credit providers should provide financial/credit education before advancing credit to them, and that stringent conditions including provision of collaterals should form parts of digital loan agreement so that only financial/credit knowledgeable and serious deserving applicants that can repay loan have access to it.